The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ppa.s242141
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Influencing Factors of Health-Seeking Preference and Community Health Service Utilization Among Patients in Primary Care Reform in Xiamen, China</p>

Abstract: Introduction: Patients often seek healthcare at general hospitals rather than at community healthcare centres (CHCs) which leads to inefficiency of health services. The primary healthcare reform developed by Xiamen has proven to break through the barriers of hierarchical diagnosis and treatment. The influencing factors of health-seeking behaviours of patients in the Xiamen reform, however, are unclear.Objective: This study aimed to assess patients' healthcare-seeking preferences and CHCs utilization, and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
1
25
1
Order By: Relevance
“…This is consistent with another study showing that students with higher monthly income show more favorable attitudes towards healthcare than those with lower income [18]. Research about primary care also found out that patients with higher household incomes are more willing to use community healthcare centers [17]. Income, as well as education and occupation, as important components of socioeconomic status, are all in uencing factors of health-seeking behavior [19,20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with another study showing that students with higher monthly income show more favorable attitudes towards healthcare than those with lower income [18]. Research about primary care also found out that patients with higher household incomes are more willing to use community healthcare centers [17]. Income, as well as education and occupation, as important components of socioeconomic status, are all in uencing factors of health-seeking behavior [19,20].…”
Section: Discussionsupporting
confidence: 88%
“…Smoking is considered one of the health risk behaviors which are linked to physical and psychological problems. Since smoking exposes individuals to greater health problems, it should increase health-seeking behavior [17]. However, this study nds the opposite effect among nursing students.…”
Section: Discussioncontrasting
confidence: 55%
“…Another study by Ovbiagele et al (43) found that nearly 70% of 144 stroke survivors maintained regular exercise upon being discharged from hospital, which was similar to but slightly higher than our ndings. Despite differences in research design, cultural background, and economical level, lack of conventional management(44), not ideal health care seeking behavior (45) have been main barriers for adherence behavior, and it is likely to present an even greater in uence on Chinese community-dwelling stroke survivors' long-term outcomes over the next few decades.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have evaluated the effects of public hospital reform by comparing the proportion of patients at each level, of both hospital pre-reform and post-reform, with large-scale statistical data, or by surveying the change of patient attitudes toward primary care use after the reform [30,31]. For instance, Wu et al, (2017) examined public views toward the choice of first-contact care in the hierarchical medical system of China [7].…”
Section: Reforms For Optimizing Hospital Utilization In China Since 2009mentioning
confidence: 99%